Wolf attacks on livestock, and its impact on attitudes towards wolves in Sweden - Rogers, Hanna (2014)
Conflicts between humans and wildlife are a problem in todays society. An important factor in this conflict is predation on livestock by mammalian carnivores. In Sweden this conflict is mainly focused on wolves (Canis lupus) and how people perceive wolves. The main prey for wolves in Sweden is the moose (Alces alces), but predation on livestock also occurs. Attitudes towards wolves are influenced by a number of things. Proximity, social group, education, if the person is a hunter or not and negative experience are factors that can influence attitudes. Negative experience could be an important factor due to non-consumptive effects. Non-consumptive effects are indirect effects on a prey animal in response to the presence of a predator. These effects could result in weight loss, impaired reproduction, stress and vulnerability to infections in the affected animal. All this could lead to economic losses for the livestock owner and may result in a negative attitude. The aim of this study was to assess if positive attitudes towards wolves could be influenced by the number of attacked animals in Sweden between the years 2004 and 2009. The aim was also to discuss other factors that could influence attitudes and if non-consumptive effects could be of importance. The results showed that the positive attitudes on a national level had increased as had the number of attacked animals. In most of the counties with established predator populations the positive attitudes had decreased while the number of attacked animals had increased. However, the number of attacked animals in these counties fluctuated and did not seem to be in accordance with the attitudes. The results indicated that the number of attacked animals was not a strong factor in determining attitudes, and that other factors seem to be of more importance. Other factors could be proximity, since in the counties with more than one wolf territory the attitudes had decreased; social group, people in ones surrounding have an influence on your opinions, and/or if the ...